2022
DOI: 10.47197/retos.v46.93336
|View full text |Cite
|
Sign up to set email alerts
|

Effects of taekwondo on health in older people: a systematic review

Abstract: Objective: This study aimed to identify the effects of taekwondo on health in elderly individuals. Methods: A systematic literature review was conducted following the PRISMA recommendations and registered on PROSPERO, as number CRD42021279561. The electronic databases MEDLINE (via PubMed), Scopus, SPORTDiscus, and Web of Science were searched, with the Medical Subject Headings (MeSH) terms “martial arts” and “aged” and the alternative terms “taekwondo”, “elderly”, and “older”. We included studies that analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The exercise methods selected in this study showed that BMD or biochemical markers that stimulate bone metabolism benefit from the improvement of the evaluated bone structures, mainly the lumbar spine, femur, and hip. The results of this study corroborate what the scientific literature has robustly shown, that is, that physical exercise promotes improvements in BMD (Borba-Pinheiro et al, 2016;D.G. Linhares et al, 2022;Souza et al, 2021;Swain, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…The exercise methods selected in this study showed that BMD or biochemical markers that stimulate bone metabolism benefit from the improvement of the evaluated bone structures, mainly the lumbar spine, femur, and hip. The results of this study corroborate what the scientific literature has robustly shown, that is, that physical exercise promotes improvements in BMD (Borba-Pinheiro et al, 2016;D.G. Linhares et al, 2022;Souza et al, 2021;Swain, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…However, even the practice of choreographed Taekwondo movements involves the delivery of powerful techniques in which skill and grade progression are limited by the physical abilities of the older participants (Brudnak et al., 2002). Furthermore, while studies on Taekwondo have shown balance improvements and reduced falls risks, the intervention methods were mostly different in each study, casting uncertainty on which components of Taekwondo training is most beneficial (Linhares et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Circuit training is a form of conditioning that combines highintensity resistance and aerobic training (Martins et al, 2020). It is designed to be easy to follow and targets strengthbuilding as well as muscular endurance (Linhares et al, 2022). Based on the problems that have been developed previously, the purpose of this study is to determine the difference in the effect of the circuit method of body weight training between the treatment group and the control group on cardiovascular endurance.…”
Section: Introductionmentioning
confidence: 99%